Performance analysis of the Level control with inverse response by using particle swarm optimization - I. M. Chew; Felisa Wong; Awang Bono; Jobrun Nandong; K. I. Wong (2020)
Boiler is an important utility system to support operations in the industry. The control of water level in the steam drum is a complicated task due to the non-minimum phase (NMP), which possibly will cause instability to the controlled water level in the steam drum. Process identification and controller design are difficult tasks for the steam drum because of non-minimum phase. Following the previous literature, this paper proposed process identification to 3rd order transfer function and optimization of Proportional-Integral-Derivative (PID) tunings of the water level by using Particle Swarm Optimization (PSO). A Graphical User Interface (GUI) has been developed to provide a direct platform to deal with these tasks. The result of PSO is compared with other tuning methods in terms of performance indicator and index. An analysis of the performance curve in 3-dimension graphs is also presented to visualize the output performance of various proportional and integral gain settings. The study has concluded that PSO provided better PI tunings for the best control of the Heat Exchanger function in the LOOP-PRO software.